THE INFLUENCE OF INTELLECTUAL CAPITAL, TECHNOLOGY, AND GROWTH OPPORTUNITY ON COMPANY VALUE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE (A STUDY OF TECHNOLOGY & TELECOMMUNICATIONS SECTOR COMPANIES LISTED ON THE IDX FOR THE 2021-2024 PERIOD) - Diana Retno Furi; Sigit Hermawan (Antis Publisher, 2026)
Objective: This study aims to analyze and obtain empirical evidence regarding the influence of intellectual capital, technology, and growth opportunities on firm value in technology sector companies listed on the Indonesia Stock Exchange. Furthermore, this study also aims to examine the role of Good Corporate Governance as a moderating variable in the relationship between intellectual capital, technology, and growth opportunities on firm value. Method: This is a quantitative study with an explanatory approach. The population in this study was all 40 technology companies listed on the IDX during the 2021–2024 period. The data analysis technique used in this study was Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Results: The results show that all independent variables, namely intellectual capital, technology, and growth opportunities, have a positive and significant influence on firm value. Among these three variables, growth opportunities are proven to have the most dominant influence in increasing firm value, indicating that growth prospects are a primary consideration for investors in assessing companies. Furthermore, Good Corporate Governance not only has a direct influence on firm value but also acts as a moderating variable that strengthens the relationship between intellectual capital, technology, and growth opportunities on firm value. This confirms that good corporate governance can optimize the use of a company's strategic resources, thereby creating greater value. Novelty: Thus, this study strengthens the integration of theories such as Resource-Based Theory and Knowledge-Based View in explaining the determinants of firm value.